أثر الهيكل التنظيمي على فاعلية الإدارة الاستراتيجية "دراسة ميدانية على الشركة العامة لمرفأ طرطوس" - ديوب, محمد; زهره, احمد (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يهدف هذا البحث إلى دراسة أثر الهيكل التنظيمي بأبعاده الثلاثة ( التعقيد، الرسمية، المركزية) على فاعلية الإدارة الاستراتيجية في الشركة العامة لمرفأ طرطوس. ولتحقيق هذا الهدف تم تطوير استبانة لتحقيق هذا الهدف، حيث تم توزيع الاستبانة على عينة البحث المتمثلة بالمديرين ( في كافة المستويات )،وقد استخدم الباحث المنهج الوصفي في جمع البيانات وتم الاعتماد على برنامج التحليل الإحصائي spss.20)) في تحليلها.وتوصل الباحث إلى عدة نتائج منها: إن هناك علاقة إيجابية بين المتغيرات المستقلة (التعقيد والرسمية والمركزية في الهيكل) على المتغير التابع (فاعلية الإدارة الاستراتيجية) حيث بلغت قيمة معامل الارتباط بين المتغيرات المستقلة والمتغير التابع 82% ، ومعامل التحديد 67% باعتبار المرفأ منشأة حكومية ذات حجم كبير، وتخضع لأنظمة وقوانين وتعليمات صارمة، وتعمل في بيئة عمل مستقرة.وأوصى الباحث بضرورة إعادة تصميم الهيكل التنظيمي في الشركة العامة لمرفأ طرطوس ليتناسب مع تطبيق الإدارة الاستراتيجية بفاعلية ، إضافة إلى تشجيع الاتصالات الرأسية والأفقية والتنظيم غير الرسمي لينعكس ذلك إيجاباً على العاملين،ومن ثم على فاعلية المنظمة.This research aims to study the effect of the organizational structure of the three dimensions(complexity, official, central) on the effectiveness of strategic management at the General Company of Tartous Port, To achieve this goal, a questionnaire was developed to achieve this goal, where the questionnaire was distributed to the research sample of managers (at all levels), The researcher used the descriptive approachin data collection, it was relying on statistical analysis program (spss.20) in its analysis. The researcher found many results such: There is a positive relationship between independent variables ( complexity, official, and central in structure) of the dependent variable (effectiveness of strategic management), the value of the correlation coefficient between independent variables and dependent variable 82% , and coefficient of determination 67%, considering the port is a government company with a large volume and subject to the laws, regulation, and strict instruction. And works in a stable environment .The researcher recommended the need to redesign the organizational structure of the general company of Tartous port to suit the application of strategic management effectively, in addition the promotion of vertical and horizontal organization and informal communications as reflected positively on the workers, and thus the effectiveness of the organization.